The Role of Teacher Leadership in the Independent Curriculum Learning Process - Sikumbang, Syilfy Adha; Simbolon, Ronti; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
As a leader in education, a teacher must be a leader who is liked, trusted, and able to guide students to grow and develop into humans who are ready to adapt and face challenges. The independent curriculum comes with a student-centered learning system, the teacher is not the only source of knowledge. So what is the role of teachers in independent curriculum learning? This research aims to describe a literature review regarding the role of teacher leadership in independent curriculum learning. The method used in this research is a qualitative method with a type of literature review which will conduct research by summarizing several materials sourced from journals, books and other sources related to the role of teachers and the independent curriculum in learning in Indonesia. In the learning process, although it is not teacher-centered, the teacher still has control over the course of the learning process. Teachers are responsible for planning instruction including setting goals and objectives, selecting materials and activities and assessing student learning. So it can be concluded that teachers have an important role in the independent curriculum learning process.